Problem And Principles Of Surgical Treatment Of Haemangiomas - Dr. Mita Prasanna (Indian Journal of Plastic Surgery, 1992)
Surgical excision of haemangiomas in selected cases is the quickest and surest method of cure. However, this treatment modality has never been very popular because of problems of bleedings, recurrence and need for reconstruction later. A study of 25 cases of various types of haemangiomas treated surgically is presented.